2014
DOI: 10.1128/aac.01685-13
|View full text |Cite
|
Sign up to set email alerts
|

Amidate Prodrugs of 9-[2-(Phosphonomethoxy)Ethyl]Adenine as Inhibitors of Adenylate Cyclase Toxin from Bordetella pertussis

Abstract: Adenylate cyclase toxin (ACT) is the key virulence factor of Bordetella pertussis that facilitates its invasion into the mammalian body. 9-[2-(Phosphonomethoxy)ethyl]adenine diphosphate (PMEApp), the active metabolite of the antiviral drug bis(POM)PMEA (adefovir dipivoxil), has been shown to inhibit ACT. The objective of this study was to evaluate six novel amidate prodrugs of PMEA, both phenyloxy phosphonamidates and phosphonodiamidates, for their ability to inhibit ACT activity in the J774A.1 macrophage cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Bisamidate prodrugs with L-phenylalanine isopropyl ester were used based on their significantly improved stability in plasma and decreased cytotoxicity compared to the original adefovir dipivoxil (bis(POM)PMEA). 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisamidate prodrugs with L-phenylalanine isopropyl ester were used based on their significantly improved stability in plasma and decreased cytotoxicity compared to the original adefovir dipivoxil (bis(POM)PMEA). 43 …”
Section: Discussionmentioning
confidence: 99%
“…1), with enhanced plasma stability profile and low toxicity were evaluated as potentially more suitable drug candidates for antitoxin therapy despite their somewhat lower efficacy to inhibit ACT compared with bis(POM)PMEA ( I ). 43 Based on these results, 43 and taking into account various aspects of the prodrug strategy (stability, cytotoxicity, cell membrane permeability, ease of synthesis and handling), L-phenylalanine isopropyl ester moiety (as in compound III , Fig. 1) has been selected as a representative type of bisamidate prodrug for the evaluation of any other novel nucleotide analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was found that PMEApp is also a potent inhibitor of bacterial ACs, and crystal structures of EF–calmodulin and ACT–calmodulin with PMEApp were resolved. Recently, Česnek et al . studied a series of amidate prodrugs of PMEA and selected the corresponding isopropyl ester l ‐phenylalanyl derivative III (Figure ) as a promising type of prodrug considering its in vitro activity, bioavailability and synthetic accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…12 In general, ANPs have ability to target various metabolic pathways where they exhibit a wide range of biological activities, e.g. antibacterial, immunomodulatory and antineoplastic 13,14,15,16,17 and can serve as monomers for oligonucleotide synthesis. 18 Figure 2.…”
Section: Introductionmentioning
confidence: 99%